In vivo and cellular antiarrhythmic and cardiac electrophysiological effects of desethylamiodarone in dog cardiac preparations. (23rd February 2022) - Kohajda, Zsófia; Virág, László; Hornyik, Tibor; Husti, Zoltán; Sztojkov‐Ivanov, Anita; Nagy, Norbert; Horváth, András; Varga, Richárd; Prorok, János; Szlovák, Jozefina; Tóth, Noémi; Gazdag, Péter; et al.
Abstract : Background and Purpose: The aim of the present study was to study the antiarrhythmic effects and cellular mechanisms of desethylamiodarone (DEA), the main metabolite of amiodarone (AMIO), following acute and chronic 4‐week oral treatments (25–50 mg·kg −1 ·day −1 ). Experimental Approach: The antiarrhythmic effects of acute iv. (10 mg·kg −1 ) and chronic oral (4 weeks, 25 mg·kg −1 ·day −1 ) administration of DEA were assessed in carbachol and tachypacing‐induced dog atrial fibrillation models. Action potentials were recorded from atrial and right ventricular tissue following acute (10 μM) and chronic (p.o. 4 weeks, 50 mg·kg −1 ·day −1 ) DEA application using the conventional microelectrode technique. Ionic currents were measured by the whole cell configuration of the patch clamp technique in isolated left ventricular myocytes. Pharmacokinetic studies were performed following a single intravenous dose (25 mg·kg −1 ) of AMIO and DEA intravenously and orally. In chronic (91‐day) toxicological investigations, DEA and AMIO were administered in the oral dose of 25 mg·kg −1 ·day −1 ). Key Results: DEA exerted marked antiarrhythmic effects in both canine atrial fibrillation models. Both acute and chronic DEA administration prolonged action potential duration in atrial and ventricular muscle without any changes detected in Purkinje fibres. DEA decreased the amplitude of several outward potassium currents such as IKr, IKs, IK1, Ito, and IKACh, while the ICaL and late INa inward currents were also significantly depressed. Better drug bioavailability and higher volume of distribution for DEA were observed compared to AMIO. No neutropenia and less severe pulmonary fibrosis was found following DEA compared to that of AMIO administration. Conclusion and Implications: Chronic DEA treatment in animal experiments has marked antiarrhythmic and electrophysiological effects with better pharmacokinetics and lower toxicity than its parent compound. These results suggest that the active metabolite, DEA, should be considered for clinical trials as a possible new, more favourable option for the treatment of cardiac arrhythmias including atrial fibrillation.